The Effects of Modifying Peanut Shell Powder with Polyvinyl Alcohol on the Properties of Recycled Polypropylene and Peanut Shell Powder Composites - Nor Fasihah Zaaba; Hanafi Ismail; Mariatti Jaafar (BioResources, 2014)
The effects of the chemical modification of peanut shell powder (PSP) using polyvinyl alcohol (PVOH) were studied. Both modified and unmodified peanut shell powder were used to prepare recycled polypropylene (RPP) and PSP composites. The effects of various PSP loadings (0 to 40% by weight) on the processing, tensile properties, morphology, Fourier transform infrared (FTIR) spectra, and water uptake properties were examined. Results showed that RPP composites with polyvinyl alcohol-modified PSP had higher values of tensile strength, elongation at break, and tensile modulus, but lower water resistance, than RPP composites with unmodified PSP. FTIR analysis revealed slight changes in band positions and intensities, indicating a distinct interaction between hydroxyl groups of the PSP composites and PVOH. RPP composites with PSP modified with PVOH had better interfacial adhesion between the matrix and the filler than RPP composites with unmodified PSP, as shown by scanning electron microscope (SEM) micrographs.